Pharmacological aspects of nursing care - Broyles, Bonita E.; Evans, Mary E. , 1942-; Reiss, Barry S. , 1944- (Cengage Learning, 2013)
Revision of: Pharmacological aspects of nursing care / Barry S. Reiss, Mary E. Evans. 4th edition. c1993